Relationships Between Social Norms, Social Network Characteristics, and HIV Risk Behaviors in Thailand and the United States - Carl Latkin (2018)
Objective: Social norms have been associated with a wide range of health behaviors. In this study, the authors examined whether the social norms of HIV risk behaviors are clustered within social networks and whether the norms of network members are linked to the risk behaviors of their social network members. Design: Data were collected from the baseline assessment of 354 networks with 933 participants in a network-oriented HIV prevention intervention targeting injection drug users in Philadelphia, United States, and Chiang Mai, Thailand. Main Outcome Measures: Four descriptive HIV risk norms of sharing needles, cookers, and cotton and front- or back-loading among friends who inject were assessed. Results: Three of 4 injection risk norms (sharing needle, cookers, and cotton) were found to be significantly clustered. In Philadelphia, 1 network member's (the index participant) norms of sharing needles and front- or back-loading were found to be significantly associated with the network members' risk behaviors, and the norm of sharing cotton was marginally associated. Conclusion: The results of this study suggest that among injection drug users, social norms are clustered within networks; social networks are a meaningful level of analyses for understanding how social norms lead to risk behaviors, providing important data for intervening to reduce injection-related HIV risks. © 2009 American Psychological Association.